Customer satisfaction and loyalty in service brand - Hashim, S.; Che Ha, N. (2008)
Combined with the identified uniqueness of services and the growing prominence of service marketing, brand equity is applicable in managing the brand associations (Settle, 1989). Strong brand equity allows company to enjoy high brand satisfaction and strong brand loyalty associations with customers (Schuler, 2002).Therefore, this study sets out to investigate the service brand relationship towards the customer satisfaction and loyalty in the context of banking services. This study employed a six scale questionnaire survey design based on the service brand equity concept introduced by (O'Cass, 2002) which focusing on consumer based perceptions of brand associations of a service brand. Data was then analyzed using means and correlation analysis. The finding about customer service satisfaction and service loyalty displayed significant relationships. The correlation indicated that service brand satisfaction is able to predict a particular outcome such as services loyalty and the mean explains 74.6%(Pearson ) and 72.1% (Spearman) of the variance in the correlation. The survey was administered to 259 commercial bank users intercepted on a University Malaya Campus, Kuala Lumpur, Malaysia. Nevertheless the finding has important implications to management and academia. A practical application from this study would be the use of certain dimensions in service brand avenues may be more effective in enhancing positive customer outcomes.